Study of the August 2010 heat event in Cyprus - Retalis, Adrianos; Paronis, Dimitrios; Michaelides, Silas; Tymvios, Filippos; Charalambous, D.; Hadjimitsis, Diofantos G.; Agapiou, Athos (My University, 2013)
An intense heat wave lasting for several days occurred in Cyprus during August 2010. Record high surface air temperatures were monitored. The aim of this study is to present the intensity and spatial extent of this event for four major districts, based on the analysis of MODIS Aqua satellite images along with surface air temperature data. Emphasis was given in the estimation of the urban heat island intensity and the differences from the respective mean intensity for August 2002–2008.
Keywords: Heat Wave; Land Surface Temperature; Urban Heat Island; Urban Heat Island Intensity; Heat Wave Event